2016
DOI: 10.1073/pnas.1521645113
|View full text |Cite
|
Sign up to set email alerts
|

Molecular tandem repeat strategy for elucidating mechanical properties of high-strength proteins

Abstract: Many globular and structural proteins have repetitions in their sequences or structures. However, a clear relationship between these repeats and their contribution to the mechanical properties remains elusive. We propose a new approach for the design and production of synthetic polypeptides that comprise one or more tandem copies of a single unit with distinct amorphous and ordered regions. Our designed sequences are based on a structural protein produced in squid suction cups that has a segmented copolymer st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
113
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 68 publications
(116 citation statements)
references
References 36 publications
3
113
0
Order By: Relevance
“…In light of these studies, it has been recently demonstrated that it is possible to control and improve the physical properties (i.e., mechanical and thermal) of SRT-based biopolymers using a specific polypeptide sequence for both crystalline and amorphous regions. [21] Heterologous expression of these tandem repeat proteins in bacteria has enabled bulk synthesis of these unique biopolymers ( Figure 1B). Genes for these tandem-repeat SRT proteins are synthesized via a modified rolling-circle-amplification method.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In light of these studies, it has been recently demonstrated that it is possible to control and improve the physical properties (i.e., mechanical and thermal) of SRT-based biopolymers using a specific polypeptide sequence for both crystalline and amorphous regions. [21] Heterologous expression of these tandem repeat proteins in bacteria has enabled bulk synthesis of these unique biopolymers ( Figure 1B). Genes for these tandem-repeat SRT proteins are synthesized via a modified rolling-circle-amplification method.…”
Section: Resultsmentioning
confidence: 99%
“…Tandem repeat proteins was prepared following protocol reported by Jung et al [21] Protein expression is initiated by a single colony, which was inoculated and grown overnight in 5mL of LB with ampicillin (100 µg/mL). The overnight culture were scaled up to 2 L (i.e., four 500mL LB media) and was grown on a shaker at 210 rpm and 37°C for 5 hours.…”
Section: Protein Expression Of Tandem Repeat (Tr) Proteinsmentioning
confidence: 99%
See 2 more Smart Citations
“…This manipulability enables the mechanical properties of protein‐based materials to be improved in a manner analogous to synthetic polymers. Many repeat sequences have been chosen as building blocks and are repeated to generate high molecular weight and enhance mechanical properties . Genetically engineered silk‐like proteins (GAGAS of silkworm and GPGXX of spider), elastin‐like protein (GVGVP), and resilin (GGRPSDSYGAPGGGN) are representative examples of repeat sequences that have been engineered for scaffolding biomaterials based on high tensile strength and/or deformability.…”
Section: Introductionmentioning
confidence: 99%